E-commerce website photography equipment / Khairul Ihsan Sudin - Sudin, Khairul Ihsan (2013)
Photography has become one ofthe new trends in this country. The number of website that sells photography equipment in Malaysia is not as many as overseas. With the growth of e-Commerce, there is a growing ofthe websites of Photography Equipment. To accomplish the study, questionnaire has been distributed.to the photography user to get the feedback on developing this project. The proposed project is developed based on Waterfall Model. The implementation of e-Commerce Website Photography Equipment targets to improve the website by creating the 3D images of the products in order to give more real feeling when the user viewing the product images and also expand the system to be more user friendly by giving the user some space to give any suggestion about the e-Commerce Website Photography Equipment. The concept will enable the viewers to visit the website and buy the product in it.